Relationship Between Mobility and Arousal Level After Waking Up. Issue 1 (January 2016) - Wakasa, Masahiko; Uemura, Sachiko; Ito, Wakako
Abstract : Background and Purpose: Falling is an unexpected event for older adults, but few studies have investigated falls related to arousal levels and mobility immediately after waking up in the morning. Therefore, the purpose of this study was to clarify the possible relationship of arousal level and mobility with falls in the early morning hours. Methods: We investigated both arousal levels and mobility of 14 community-dwelling older adults after waking up, from 4:00 AM until 2:00 PM. Mobility and arousal levels were evaluated through the following tests: Timed Up and Go, Functional Reach, postural sway, and critical frequency of fusion. Baseline of mobility and arousal levels were measured before sleep and after 5 hours of sleep. Immediately after waking up, each participant's mobility and arousal levels were remeasured and then also remeasured 2 hours later, 6 hours later, and 10 hours later, respectively. Stanford Sleepiness Scale was also chosen to measure the internal state of subjective sleepiness and it was measured 7 times at 2-hour intervals after the participants woke up from sleep. Results: Significant differences were found between before sleep and after awakening in the score of Timed Up and Go test and Stanford Sleepiness Scale. The speed of Timed Up and Go test after awaking was slower than that before sleep. The Stanford Sleepiness Scale showed high states of sleepiness. Conclusion: We found that the decrease in arousal level in the early morning may affect mobility. The awareness of the degree of arousal levels may increase fall prevention in older adults in the early morning hours.